Suicide Associated with Risk Factors in Patients Suffering from Depression - Ayub, Sher; waris, Abdul; Niaz, Hina; Ayub, Zahida; Qureshi, Nazia (Journal of Gandhara Medical and Dental Science, 2020)
OBJECTIVES: The purpose of this study was to assess suicide and their relationship with risk factors i.e. degree of hopelessness, severity of depression and suicidal ideations. METHODOLOGY: It was a cross sectional study conducted in Psychiatry unit Khyber Teaching Hospital Peshawar. The total sample of this study was forty-eight admitted patients. Those patients were included in the study that scored moderate to high in Hamilton Depression Rating Scale (HDRS), Hopelessness Scale and Reasons for Living Inventory (RLI). The collected data were analysed using SPSS version 22. RESULTS: Study showed that reasons for living as well as the subscales of reasons for living inventory i.e. responsibility towards family, hope of improvement and surviving and coping beliefs have significant inverse correlation with score on Hopelessness Scale and suicidal ideations. The score on subscale religious beliefs had significant correlation only with score on hopelessness. Married individuals’ responses were different on total reasons for living to a significant extent. The patients with past psychiatric history had significantly greater fear of suicide. The three different social groups did not differ to a significant extent in scoring on reasons for living. CONCLUSION: The reasons for living as a whole and some of the subscales of Reasons for Living Inventory have significant inverse relationship with suicidal risk factors showing the modulatory effect of these reasons on suicidal risk. Moreover, these reasons are not equally distributed among some of the sociodemographic and clinical groups.